Analysis of Factors Affecting Students' Job Readiness in Kendal Regency - Wati, Bella Mei Mulya; Khafidz, Muhammad; Latifah, Lyna (Journal of Economic Education, 2024)
Based on survey data related to the number of vocational high school graduates absorbed in the workforce is still small, this is because students feel they are not ready to work and prefer to continue their education or be unemployed. Vocational high school graduates have been prepared to enter the workforce directly after they graduate, so students' work readiness needs to be improved. This study aims to determine the effect of parental support, industrial work practices, career guidance, self-efficacy, and learning achievement on work readiness through soft skills. The population in this study were 12th-grade vocational high school students majoring in Office Management and Business Services. Determination of sample size using the Slovin formula with a sample size of 112 respondents. The sampling technique used is proportional random sampling. The data collection technique in this study used a questionnaire that had been tested for validity and reliability. The data analysis techniques used include descriptive analysis and inferential analysis based on Structural Equation Modeling (SEM) with the help of Smart PLS. The results of the hypothesis test show that of the sixteen hypotheses formulated, only three hypotheses have a positive and significant influence, namely parental support for work readiness, industrial work practices for soft skills, and learning achievement for soft skills.